Granulares de caucho: uso e implementación como aditivo en concreto y pavimentos (2021)
In the last years has been an excessive use of non-renewable materials such as rubber, especially in the tire manufacture process due to its mechanical and physical properties, resistance to abrasion and greater durability, usually when the tires finish their useful life, are discarded or otherwise are burned, also is important to know that these materials need a long period to achieve a natural degradation. Several studies have been made to investigate about the reuse of rubber at the end of its useful life, such as binders or conglomerates, in order to create innovative materials for the construction sector. This article relates different researchesthat have been made about rubber such as its origin, composition, properties, treatments and reuse processes in order to provide its possible uses in the construction sector, for this it is of great importance to know the components, physical, chemical and mechanical properties present in the rubber before, during and after the reuse processes, since by means of a correct characterization of the material, can be known and make an appropriate use of the material likean aggregate in the construction material.